Gedung Jurusan Arsitektur Universitas Riau Dengan Pendekatan Arsitektur Organik - Dian Reztika; Wahyu Hidayat; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Architecture Department Building of Riau University is building which functioned to accommodate architectural education activities. Because of the Architecture Department Building is under management of Engineering Faculty, the design of Architecture Department Building of Riau University need to be adapted with the design of other buildings in Engineering Faculty environment. To improve students comfortability in architectural creativity, organic architecture as the design approach blend the nature context into the design. Organic architecture is the architecture philosophy which present the harmony between building as the place for the people to do some activities with their environment around. Based on organic architecture principles of Frank Lloyd Wright that the nature is the main element of a design, then “organic from the trees” as the design concept gives the design solutions based on contextual issues and character of the trees as inspiration the mass concept. Contextual consideration produce the order mass, orientation of mass, landscape pattern and circulation within the site. While the mass concept inspired by the characteristics of the trees in the form of trunk, branches, twigs and branches produces a transparent foam of mass with pattern of open space and a porous mass with the facade and unique roof. The result of Architecture Department Building of Riau University design grow and develop from the existing condition of the site and harmony with the environment around of the building.Keyword: Architecture, Building, Contextual, Organic, Trees.